2019
DOI: 10.1103/physrevmaterials.3.084603
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting phase diagram and nontrivial band topology of structurally modulatedSn1xSbx

Abstract: We report the discovery of superconductivity in binary alloy Sn1−xSbx with x in the range of 0.43 to 0.6, which possesses a modulated rhombohedral structure due to the incommensurate ordering of Sn and Sb layers along the c-axis. The specific heat measurements indicate a weakly coupled, fully gapped superconducting state in this homogeneity range with a maximum bulk Tc of 1.58 K at x = 0.46, though the electronic specific heat and Hall coefficients remain nearly x-independent. The nonmonotonic dependence of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…DC magnetization measurements exhibited superconductivity below 4K. In an earlier report[15],superconductivity is observed at below 4K for x=0.43, albeit with a relatively broader transition. M-H plots at various temperatures give a clear glimpse of Type-II superconductivity in this material, neglecting the possibility that this enhanced T c may be due to Sn, which is Type-I superconductor with T c near to 3.7K.ExperimentalSn 0.4 Sb 0.6 crystal is synthesized by solid state reaction route via vacuum encapsulation in PID controlled muffle furnace.…”
mentioning
confidence: 54%
See 3 more Smart Citations
“…DC magnetization measurements exhibited superconductivity below 4K. In an earlier report[15],superconductivity is observed at below 4K for x=0.43, albeit with a relatively broader transition. M-H plots at various temperatures give a clear glimpse of Type-II superconductivity in this material, neglecting the possibility that this enhanced T c may be due to Sn, which is Type-I superconductor with T c near to 3.7K.ExperimentalSn 0.4 Sb 0.6 crystal is synthesized by solid state reaction route via vacuum encapsulation in PID controlled muffle furnace.…”
mentioning
confidence: 54%
“…Superconductivity in SnSb is reported a long time ago [17], in a joint report of intermetallic superconductors. The interest renewed once again when recently, it is been predicted from first principal density functional calculations [15] that same may be a TS and a detailed report showing bulk superconductivity in SnSb appeared in 2018 [18]. In a recent study it has been shown that critical temperature can be tuned in SnSb by changing the elemental composition viz Sn 1x Sb x .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…type II superconductor below 1.5 K at x=0.5 [26][27][28][29]. Recently, in our previous report, there is an enhancement in the superconducting critical temperature at x=0.4.…”
Section: Introductionmentioning
confidence: 71%